(untitled) (Global Journal of Management and Business Research, 2017)
The aim of this study is to assess the role of risk management on financial performance in Rwanda institutions: Case study of UNGUKA Bank Ltd undertaken within period 2012-2016. The data was collected through a questionnaire designed for 30 staffs members of Unguka Bank Ltd where both quantitative and qualitative techniques were employed. The interviews were conducted with key informants from like the Unguka bank ltd staffs. Findings shows that the determinants of risk management in Unguka bank Ltd are credit risk, operational risk, interest rate and liquidity risk are the determinants of risk management. The results shows that Unguka bank Ltd is profitable during the covered period because the standard ratio of return on asset is 1% may factors are the cause of that profitability but the quality service are the main cause of the increase of its profitability. The researcher also found out that there is a very strong relationship between risk management and financial performance.